Development of Electronic Student Worksheet (E-Worksheet) Based on Project Based Learning (PJBL) to Train Student's Critical Thinking Skills on Biotechnology Topic of 10th Grade in Senior High School - Fitriandini, Monica Salma; Isnawati, Isnawati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
The Ministry of Education, Culture, Research and Technology (Kemendikburistek) has issued the latest policy regarding the Merdeka Curriculum. The Merdeka Curriculum seeks to answer the education issues in the context of the Industrial Revolution 4.0. Which, in its realization, students need critical thinking skills. PISA statistical data shows students’ critical thinking skills are still relatively low. Innovative teaching material and the right learning model are required. This research was conducted to develop an E-Worksheet based on ProjectBased Learning regarding validity, practicality and effectivity to train critical thinking skills. This research involved 20 students in 10th grade in SMA Negeri 1 Taman, Sidoarjo. The results showed that the validity of the E-Worksheet was obtained with an average percentage value of overall validity of 98.81% with a very valid category. The practicality of E-Worksheet was reviewed in two ways: the results of observations of E-Worksheet implementation, which obtained an average percentage of 95% with a with a very practical category and the results of the response questionnaire, which obtained an average percentage of 97% with a very practical category. The effectivity of the E-Worksheet was reviewed based on the learning outcomes score. The data obtained results from working on pre-test and post-test questions, which received a percentage of completeness of 100% and got an N-gain score of 0.79 with a very effective category, demonstrating the high confidence in the effectivity of E-Worksheet.